Effect of vitamin D3 treatment on endothelial function in obese adolescents. Issue 4 (14th August 2015) - Javed, A.; Kullo, I. J.; Balagopal, P. Babu; Kumar, S.
Summary: Background: Obesity in children is associated with vitamin D deficiency and endothelial dysfunction. It is not known if treatment with vitamin D improves endothelial function in obese adolescents. Objective: This study aimed to determine whether treatment with vitamin D3 improves endothelial function in obese adolescents. Methods: Nineteen obese adolescents, 13–18 years of age, with 25‐hydroxy vitamin D (25[OH]D) levels <75 nmol L −1 were treated with 100 000 IU vitamin D3 orally once a month for 3 months in an open‐label, single‐centre prospective trial. Endothelial function was assessed by flow‐mediated dilatation (FMD) of the brachial artery at study entry and 1 month after the third dose of vitamin D3 . Biochemical parameters, including calcium, fasting lipids, glucose, insulin and high‐sensitivity C‐reactive protein, were also obtained. Results: Mean 25(OH)D levels increased from 55.9 ± 12.2 to 86.9 ± 16.7 nmol L −1 ( P  < 0.01). There was no correlation between 25(OH)D levels and brachial artery FMD. The brachial artery FMD (%) did not change significantly following vitamin D3 treatment (9.5 ± 3.53 vs. 10.3 ± 3.83, P  = 0.83). Serum parathyroid hormone declined from 3.8 ± 1.5 to 3.1 ± 1 pmol L −1 ( P  = 0.01). The remainder of biochemical measurements did not show a significant change. Conclusions: Treatment with vitamin D3, 100 000 IU once a month for 3 months was effective in increasing 25(OH)D levels in obese adolescents but did not impact endothelial function.